2020
DOI: 10.1155/2020/7917965
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Resistance and Its Associated Factors among People with Bipolar Disorder at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia

Abstract: Background. Stigma resistance is the capacity to cope and remain unaffected by mental illness stigmatization. In bipolar patients, having low stigma resistance may result in a higher internalized stigma, low self-esteem, and poor treatment outcome. In Ethiopia, the prevalence of stigma resistance among bipolar patients is not well known. Therefore, this study is aimed at assessing the prevalence of stigma resistance and its associated factors among bipolar patients at Amanuel Mental Specialized Hospital, Addis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…The analysis of available studies revealed that many factors could effectively predict stigma in people living with bipolar disorders and their families, including social and cultural structures, inefficient welfare system, low education, unemployment or lack of a suitable job, low self-esteem, poor communication skills, lack of intimate relationships with others, lack of being understood by others, poor social support, collectivist cultures, young age at disease onset, recurrent hospitalizations, gender, disease severity, disease duration, discriminative labels, lack of information/knowledge, generalization, banalization and reaction induced by public stigma in the general population, or among professionals such as health care professionals and employers. This finding was consistent with the results of Bonnington, Clemente, Favre, Sadeghi, Engidaw, Shumet, Thome, Cerit, Sarisoy, Howland, Ellison, Nilsson and Pal (Bonnington & Rose 2014 ; Clemente et al 2017 ; Favre et al 2022 ; Sadeghi et al 2003 ; Engidaw et al 2020 ; Shumet et al 2021 ; Thomé et al 2012 ; Cerit et al 2012 ; Sarısoy et al 2013 ; Howland et al 2016 ; Ellison et al 2015 ; Nilsson et al 2016 ; Pal 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…The analysis of available studies revealed that many factors could effectively predict stigma in people living with bipolar disorders and their families, including social and cultural structures, inefficient welfare system, low education, unemployment or lack of a suitable job, low self-esteem, poor communication skills, lack of intimate relationships with others, lack of being understood by others, poor social support, collectivist cultures, young age at disease onset, recurrent hospitalizations, gender, disease severity, disease duration, discriminative labels, lack of information/knowledge, generalization, banalization and reaction induced by public stigma in the general population, or among professionals such as health care professionals and employers. This finding was consistent with the results of Bonnington, Clemente, Favre, Sadeghi, Engidaw, Shumet, Thome, Cerit, Sarisoy, Howland, Ellison, Nilsson and Pal (Bonnington & Rose 2014 ; Clemente et al 2017 ; Favre et al 2022 ; Sadeghi et al 2003 ; Engidaw et al 2020 ; Shumet et al 2021 ; Thomé et al 2012 ; Cerit et al 2012 ; Sarısoy et al 2013 ; Howland et al 2016 ; Ellison et al 2015 ; Nilsson et al 2016 ; Pal 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Data were collected by interviewing the selected study participants and reviewing medical records using a validated questionnaire which was adapted from the following studies 12–15. WHO’s Composite International Diagnostic Interview suicide manual was used to assess suicidal ideation and attempt 12.…”
Section: Methodsmentioning
confidence: 99%
“… 12–15 WHO’s Composite International Diagnostic Interview suicide manual was used to assess suicidal ideation and attempt. 12 Depression was assessed using the Patients Health Questionnaire version-9 13 while social support was measured using the Oslo Social Support scale 14 and stigma related to HIV/AIDS was assessed by the perceived HIV stigma scale. 15 The reliability of the data was checked by Cronbach’s alpha tests.…”
Section: Methodsmentioning
confidence: 99%